Öğretmen adaylarının bilimin doğası anlayışlarının incelenmesi - (:unkn) unknown (My University, 2011)
0

Aiming at contributing to the literature and informing the program developers, this study presents research findings regarding the Turkish prospective science teachers’ understanding of the nature of science. 168 prospective elementary and secondary science teachers participated in the study. The participants’ views on the nature of science were assessed through a questionnaire. The results of the study confirmed those conducted in other countries. The findings indicated that prospective science teachers in Turkey, like their counterparts in the world, generally had uninformed views about the scientific enterprise.
Exploring nature of science understandings of Turkish pre-service science teachers
Keywords: Eğitim, Eğitim Araştırmaları